The Effect of Forensic Auditor Skills, Forensic Auditor Techniques, Forensic Auditor Experience, and Technological Readiness on Fraud Detection - Murry Cortinah; Herman Ruslim (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to analyze the effect of auditor skills, auditor techniques, auditor experience, technology readiness, and auditor independence. Forensic auditors are increasingly being challenged to be able to detect fraud that is increasingly sophisticated and involves aspects of the latest technology. This research approach is quantitative. The sampling technique is incidental sampling. The population is forensic auditors scattered throughout Indonesia.The primary data collection technique is the survey method. The data analysis technique used SEM-PLS.The results showed that auditor skills, forensic auditor techniques, and experience of forensic auditors partially had a positive and significant effect on fraud detection. Meanwhile, auditor technology readiness, and auditor independence, partially have a negative and significant impact on fraud detection.